Complex Evolution of 7E Olfactory Receptor Genes in Segmental Duplications - Newman, Tera; Trask, Barbara J. (Genome Research, 2003)
Large segmental duplications (SDs) constitute at least 3.6% of the human genome and have increased its size, complexity, and diversity. SDs can mediate ectopic sequence exchange resulting in gross chromosomal rearrangements that could contribute to speciation and disease. We have identified and evaluated a subset of human SDs that harbor an 88-member subfamily of olfactory receptor (OR)-like genes called the 7Es. At least 92% of these genes appear to be pseudogenes when compared to other OR genes. The 7E-containing SDs (7E SDs) have duplicated to at least 35 regions of the genome via intra- and interchromosomal duplication events. In contrast to many human SDs, the 7E SDs are not biased towards pericentromeric or subtelomeric regions. We find evidence for gene conversion among 7E genes and larger sequence exchange between 7E SDs, supporting the hypothesis that long, highly similar stretches of DNA facilitate ectopic interactions. The complex structure and history of the 7E SDs necessitates extension of the current model of large-scale DNA duplication. Despite their appearance as pseudogenes, some 7E genes exhibit a signature of purifying selection, and at least one 7E gene is expressed.[Supplemental material is available online atwww.genome.org.]
10.1101/gr.769003